A self-healing stainless steel: Role of nitrogen in eliminating detrimental effect of cold working on pitting corrosion resistance. (December 2018) - Wang, Qingchuan; Zhang, Bingchun; Ren, Yibin; Yang, Ke
Graphical abstract: Highlights: Detrimental effect was caused by the severe deformation areas with deformation bands. Nitrogen was strongly enriched in the chromium oxide layer. A self-healing reaction involving the nitrogen doping in passive film was concluded. Abstract: Nickel-free high nitrogen stainless steels (HNS) with two nitrogen contents were studied to elucidate the role of nitrogen in eliminating detrimental effect of cold working on pitting corrosion resistance. It was found that the detrimental effect was caused by the severe deformation areas with deformation bands and completely eliminated in HNS with 0.92 wt.% nitrogen. Meanwhile, nitrogen was found to be significantly enriched as a form of short range ordered [CrN] in the chromium oxide layer of the passive film. Combined with chemical compositions and semiconducting properties analysis, a self-healing reaction involving the nitrogen doping in passive film was concluded.